Pembinaan Desa Wisata Sehat Gabugan dengan melibatkan mahasiswa interprofesi dalam melatih kader Program Indonesia Sehat – Pendekatan Keluarga (PIS-PK) - Widyandana Widyandana; Tutik Kusdaryanti; Dimas Septian Eko Wahyu Sumunar; Dianing Pratiwi; Fitriana Fitriana; Nandyan Sulaksana Nugraha; Vita Yanti Anggreni; Gandes Retno Rahayu (Journal of Community Empowerment for Health, 2019)
The Government of Republic of Indonesia launched Healthy Indonesia Program with Family-Centered Approach (PIS-PK). This program intended to improve public health in commons beneath the management of public health care. However, it remains challenging for public health care to reach all families in the working area. Active participation from volunteers or cadres to encourage the implementation of this program is required. Gabugan Tourism Village is an educational tourism village in a vision to develop the concept of "healthy tourism village". Determination from the local government to achieve healthy tourism village taken by joining collaboration with Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada (FK-KMK UGM).Together with interprofessional students from the campus, local government arranged training for cadre and assist during program implementation. This study aimed to identify the Healthy Family Index (HFI) of residents in the Gabugan Tourism Village and evaluate the cadre’s level of knowledge before and after training sessions. This was action research with a quantitative descriptive method. Data collected from August 4th, 2018 to September 7th, 2018. Research subjects were family and health cadres. Sample of 50 families from 100 families population surveyed to discover Healthy Family Index (HFI), while cadres were receiving training session related to "healthy tourism villages". Pre-test and post-test followed by cadres during the training session. Survey results analyzed using quantitative descriptive, meanwhile, Wilcoxon tests set to compare pre-test and post-test scores. From 50 families an HFI average of 0.810 obtained. The highest indicator of healthy family index was access to clean water facilities and the use of healthy latrines. The lowest index found at hypertension patients taking regular medication. The results of pre-test and post-test cadres indicated rising average with value of 3,823 and p = 0,000. Families in Gabugan Tourism Village generally in the healthy group. Training program involving interprofessional students proven to significantly increase the knowledge of health cadres.